Literasi Digital bagi Siswa: Meningkatkan Kemampuan Mengintegrasikan Teknologi dalam Pembelajaran - Mulia, Mulia; Nuryanti, Dewi; Mawardi (Seumike : Society Progress Journal, 2026)
This study aims to analyze the level of students' digital literacy and its impact on the ability to integrate technology in the learning process in the era of information disruption. Using a descriptive quantitative method, this research evaluates students' competence in accessing, evaluating, and creating digital content that supports academic goals. The results show that digital literacy has a significant positive correlation with the effectiveness of technology-based learning. Despite high device access, critical evaluation skills of information still need improvement. This study concludes that strengthening digital literacy is not merely technical mastery but the formation of an adaptive mindset toward the digital ecosystem. Recommendations are provided to educational institutions to integrate digital literacy curricula across subjects.